2001
DOI: 10.1089/104303401750148847
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Rev-Independent, Minimal Simian Immunodeficiency Virus-Derived Vector System

Abstract: Lentiviral vectors are attractive candidates for gene therapy because of their ability to integrate into nondividing cells. To date, conventional HIV-1-based vectors can be produced at higher titers, but concerns regarding their safety for human use exist because of the possibility of recombination leading to production of infectious virions with pathogenic potential. Development of lentivirus vectors based on nonhuman lentiviruses constitutes an active area of research. We described a novel HIV-SIV hybrid vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The potential to exploit this property has been the principal incentive for developing viral vectors from these pathogenic complex retroviruses. After HIV-1 vectors were described, replication-defective systems were engineered from molecular clones of non-primate and other primate lentiviruses [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In addition to their use in pre-clinical gene therapy research, lentiviral vectors have been important tools for basic science [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The potential to exploit this property has been the principal incentive for developing viral vectors from these pathogenic complex retroviruses. After HIV-1 vectors were described, replication-defective systems were engineered from molecular clones of non-primate and other primate lentiviruses [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In addition to their use in pre-clinical gene therapy research, lentiviral vectors have been important tools for basic science [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…(Naldini et al, 1996;Manganini et al, 2002) and deliver genes into dividing cells at high efficiency (Tavernarakis et al, 2000;Yu et al, 2002). (Follenzi et al, 2000;Li et al, 2003;Mautino & Morgan, 2002;Mukhtar et al, 2000;Pandya et al, 2001;Qin et al, 2003;Schroers et al, 2002 Figure 5A). Furthermore, siRNA and GFP expression was observed in the CS-env-shRNA plasmid-transfected SupT1 cells for 15 days (Figures 5B,C).…”
Section: Discussionmentioning
confidence: 98%
“…The envelope cassette encodes typically, but not necessarily, for VSV-G envelope glycoprotein. The development of a fourth generation of lentiviral vectors, rev independent, has also been claimed by means of replacing RRE (rev responsive element) with heterologous viral sequences or by codon-optimization (Bray et al 1994;Delenda 2004;Kotsopoulou et al 2000;Pandya et al 2001;Roberts and Boris-Lawrie 2000). However, its use is not widespread since, contrary to the other generations of lentiviral vectors, these packaging systems have not been made available for the research community; also the reported titers are typically one to two logs bellow the maximum titers obtained with the second or third generation systems.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%